Happiness, Ideology and Crime in Argentine Cities - Rafael di Tella; Ernesto Schargrodsky (Inter-American Development Bank (IDB), 2009)
This paper uses self-reported data on victimization, subjective well being and ideology for a panel of individuals living in six Argentine cities. While no relationship is found between happiness and victimization experiences, a correlation is documented, however, between victimization experience and changes in ideological positions. Specifically, individuals who are the victims of crime are subsequently more likely than non-victims to state that inequality is high in Argentina and that the appropriate measure to reduce crime is to become less punitive (demanding lower penalties for the same crime).
Keywords: I31; K42; R29; 330; Happiness; crime; beliefs